W-types in homotopy type theory. (June 2015) - VAN DEN BERG, BENNO; MOERDIJK, IEKE
<x content-type="archive" xml:space="preserve">Abstract</x> We will give a detailed account of why the simplicial sets model of the univalence axiom due to Voevodsky also models W-types. In addition, we will discuss W-types in categories of simplicial presheaves and an application to models of set theory.